Russian Lawyers and the Soviet State : The Origins and Development of the Soviet Bar, 1917-1939 - Huskey, Eugene (Book collections on Project MUSE., 2014)
This study traces the development of the Soviet Bar through periods of legal nihilism and legal revival to its final integration into the Soviet order at the end of the 1930s--a story of uncertainty and conflict in the Bolshevik ranks over the role of the lawyer under socialism and one of resistance to Soviet power by a profession jealous of its own autonomy Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press.